Prayers for sale : [compact disc, unabridged] : a novel - Dallas, Sandra (Macmillan Audio, 2009)
Eighty-six-year-old Hennie Comfort is living in the mountains of Colorado during the Depression. Newly married Nit Spindle and her husband have recently moved to town searching for work. Hennie notices Nit wandering outside of her home, and for some reason is drawn to her. Soon their chance meeting is transformed into a deep bond where secrets and struggles are divulged.